Perbankan dan Keuangan Syariah: Tantangan dan Peluang di Pasar Global - Hardiati, Neni; Nugroho, Wahyu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The Islamic banking and finance industry in Indonesia faces significant challenges and opportunities in facing the ever-growing global market. Even though the majority of Indonesia's population is Muslim, awareness of the principles of Islamic banking and finance is still low among the public. This indicates that there are still people who do not understand sharia principles and equate sharia banks with conventional banks. Then, the complexity of regulations and sharia compliance becomes the main concern for Islamic financial institutions only the rules. However, amidst these challenges, there are great opportunities for the Islamic banking and finance industry to grow and expand market reach. By increasing public awareness, revising supportive regulations, and implementing financial technology and strategic partnerships, this industry can play a greater role in strengthening the Indonesian economy and competing in the global market. In conclusion, these strategic steps will help the Islamic banking and finance industry overcome challenges and exploit future opportunities more effectively.